The Development of Islamic Mathematics E-Comic Learning Media to Improve Students’ Mathematics Communication Skills - Mukhlis, Mohammad; Annizar, Anas Ma’ruf ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2025)
This study aims to improve students' mathematical communication skills. One way to improve students' mathematical communication skills is to develop Islamic-themed Android-based e-comic learning media. E-comics are designed to summarise material and present it in an interesting way. Therefore, this study was conducted by developing an interactive e-comic product that can improve students' mathematical communication skills. This study is a research and development study aimed at describing the validity, practicality, and effectiveness of the Islamic-themed e-comic product. The development model used is ADDIE, which consists of the following stages: analyse, design, development, implementation, and evaluation. The research subjects were 32 students in class VIII of SMPN 1 Rambipuji, along with 2 learning media experts and 2 subject matter experts as validators. The object of this study is the Pythagoras learning media using Islamic-themed e-comics. Questionnaires and surveys were used as tools to collect data. The validation score for the interactive e-comics had an average of 93%, falling into the highly valid category. The practicality of the interactive e-comics had an average of 92.5%, falling into the highly practical category. The effectiveness of the interactive e-comic had a fairly large N-gain score of 0.60, falling into the moderate category. Based on the research results obtained, it was concluded that the Islamic-themed e-comic was highly valid, highly practical, and effective in improving students' mathematical abilities.